The Use of Flow Cytometry in Myelodysplastic Syndromes: A Review - Bento, Laiz Cameirão; Correia, Rodolfo Patussi; Pitangueiras Mangueira, Cristóvão Luis; De Souza Barroso, Rodrigo; Rocha, Fernanda Agostini; Bacal, Nydia Strachman; Marti, Luciana Cavalheiro (Frontiers in Oncology, 2017)
Myelodysplastic syndromes (MDS) are a heterogeneous group of hematopoietic stem cell disease categorized by dysplasia in one or more hematopoietic cell lineages, as well as cytopenia and functional abnormalities in bone marrow cells. Several MDS classification methods have been proposed to categorize the disease and help better plan patients’ treatment. The World Health Organization (WHO) classification, released in 2008 and revised in 2016, is the currently and the most used classification method worldwide. Recent advances in MDS molecular biology and innovations in flow cytometry have enabled the development of new parameters for MDS diagnosis and classification. Several groups have published flow cytometry scores and guidelines useful for the diagnosis and/or prognosis of MDS, which are mostly based on detecting immunophenotypic abnormalities in granulocyte, monocyte and lymphoid lineages. Here, we review the current literature and discuss the main parameters that should be analyzed by flow cytometry with the aim of refining MDS diagnosis and prognosis. Furthermore, we discuss the critical role of flow cytometry and molecular biology in MDS diagnosis and prognosis, as well as the current challenges and future perspectives involving these techniques.